2018
DOI: 10.1016/j.ccell.2018.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Molecular, Pathological, Radiological, and Immune Profiling of Non-brainstem Pediatric High-Grade Glioma from the HERBY Phase II Randomized Trial

Abstract: SummaryThe HERBY trial was a phase II open-label, randomized, multicenter trial evaluating bevacizumab (BEV) in addition to temozolomide/radiotherapy in patients with newly diagnosed non-brainstem high-grade glioma (HGG) between the ages of 3 and 18 years. We carried out comprehensive molecular analysis integrated with pathology, radiology, and immune profiling. In post-hoc subgroup analysis, hypermutator tumors (mismatch repair deficiency and somatic POLE/POLD1 mutations) and those biologically resembling ple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
173
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 170 publications
(188 citation statements)
references
References 60 publications
15
173
0
Order By: Relevance
“…A retrospective study focusing on pediatric tumors demonstrated that such cases likely follow a clinical course most compatible with that of a low-grade glioma [26]. This was recently further substantiated by the post hoc sub-group analysis of the HERBY Phase II Randomized Trial [31]. …”
Section: Resultsmentioning
confidence: 99%
“…A retrospective study focusing on pediatric tumors demonstrated that such cases likely follow a clinical course most compatible with that of a low-grade glioma [26]. This was recently further substantiated by the post hoc sub-group analysis of the HERBY Phase II Randomized Trial [31]. …”
Section: Resultsmentioning
confidence: 99%
“…The addition of bevacizumab did not improve the median EFS and was associated with increased toxicity and treatment discontinuation. However, post‐hoc analyses have suggested that bevacizumab may have a role in particular subtypes of pHGG, specifically those with MAPK pathway activation and/or enhanced CD8+ T‐cell immune response . This finding illustrates the point that future randomized clinical trials should be tailored for specific biological subtypes of pHGG.…”
Section: Background Of Past Clinical Trialsmentioning
confidence: 99%
“…However, this has not been clearly defined in pHGG, where there have been inconsistent results among different studies: in the CCG‐945 and ACNS0126 cohorts, patients with MGMT‐overexpressing tumors had higher relapse rates, whereas in the ACNS0423 there was no significant difference in EFS or OS based on MGMT expression . In the HERBY trial, the methylation status of the MGMT promoter was not associated with significant differences in survival either . These discrepancies may partly stem from the fact that the use of MGMT immunohistochemistry is not as robust as other methods, such as methylation‐specific PCR and genome‐wide methylation arrays .…”
Section: Background Of Past Clinical Trialsmentioning
confidence: 99%
See 2 more Smart Citations